A C/EBPα–Wnt connection in gut homeostasis and carcinogenesis - Heuberger, Julian; Hill, Undine; Förster, Susann; Zimmermann, Karin; Malchin, Victoria; Kühl, Anja A.; Stein, Ulrike; Vieth, Michael; Birchmeier, Walter; Leutz, Achim (Life Science Alliance, 2019)
We explored the connection between C/EBPα (CCAAT/enhancer-binding protein α) and Wnt signaling in gut homeostasis and carcinogenesis. C/EBPα was expressed in human and murine intestinal epithelia in the transit-amplifying region of the crypts and was absent in intestinal stem cells and Paneth cells with activated Wnt signaling. In human colorectal cancer and murine APCMin/+ polyps, C/EBPα was absent in the nuclear β-catenin–positive tumor cells. In chemically induced intestinal carcinogenesis, C/EBPα KO in murine gut epithelia increased tumor volume. C/EBPα deletion extended the S-phase cell zone in intestinal organoids and activated typical proliferation gene expression signatures, including that of Wnt target genes. Genetic activation of β-catenin in organoids attenuated C/EBPα expression, and ectopic C/EBPα expression in HCT116 cells abrogated proliferation. C/EBPα expression accompanied differentiation of the colon cancer cell line Caco-2, whereas β-catenin stabilization suppressed C/EBPα. These data suggest homeostatic and oncogenic suppressor functions of C/EBPα in the gut by restricting Wnt signaling.
CRIS-Team Scopus Importer:2025-03-05